Word Of Mouth Marketing Strategy wom And Its Impact On Building The Image Of Institution - Bekkar, Amina (University of Eloued جامعة الوادي, 2024)
Abstract: Demand for word-of-mouth strategy marketing is in increase, With the emergence of new consumer, traditional marketing can no longer build the image of institution, this creates a gap between the new role of the consumer and the existing marketing strategies, in an increasingly competitive marketplace and abundance of choice, customers no longer trust the messages they are sent by traditional marketing channels. As a result, word-ofmouth strategy gained importance. Based on recommendations of consumers related to a product or service, word of-mouth is regarded as the most credible source of information and the most powerful tool to influence consumer to have a perfect image about the institution. Today, more and more companies have begun to include word-of-mouth in their marketing mix. For the majority, word-of mouth is known but not yet fully understood, the purpose of this paper is to provide an in- dept analysis of word-of-mouth, and their role on building the image of institution, by detecting the different techniques of this strategy as a new concept on using real experiments:
Keywords: word-of-mouth strategy; Image of an institution; Influencer marketing; marketing; marketing strategy